Mapping English Language Teacher-Researchers’ Collaboration and Networking Practices Throughout Their Professional Paths - Eva Estefania Trujeque-Moreno; Georgina Aguilar-González; Fatima Encinas-Prudencio (Profile: Issues in Teachers' Professional Development)
This article reports the findings of a multiple case study that identifies and describes the collaboration and networking practices of four Mexican English language teaching professionals belonging to two MA cohorts: 2005–2007 and 2007–2009. For two years, curriculum vitae analysis, maps, and in-depth interviews were used to collect data on these professionals’ paths. Three dimensions were examined: teaching, organization, and research, as well as levels of involvement in these professional activities, which construct and shape participants’ collaboration and networking practices. The findings revealed that each teacher-researcher’s agency was directly related to their capitalization of diverse strategies in each dimension and how this, in turn, configured their engagement in the English language teaching community or other communities.